Elective neck dissection in unilateral carcinomas of the tongue: Unilateral versus bilateral approach. Issue 4 (April 2017) - Nobis, Christopher-Philipp; Otto, Sven; Grigorieva, Tamara; Alnaqbi, Mohamed; Troeltzsch, Matthias; Schöpe, Jakob; Wagenpfeil, Stefan; Ehrenfeld, Michael; Wolff, Klaus-Dietrich; Kesting, Marco Rainer
Abstract: Purpose: Elective neck dissection (END) is a common primary treatment strategy for oral tongue squamous cell carcinoma (OTSCC), although uncertainty remains regarding the necessary extent of END for strictly unilateral early stage OTSCC. The authors evaluated two END variations, unilateral and bilateral, to determine the optimal extent. Materials and methods: A retrospective cohort study was performed on patient data from two departments of oral and maxillofacial surgery. All previously untreated patients from both clinics who were diagnosed with early-stage (pT1-2) unilateral OTSCC were included. The following variables were collected: age, gender, END type/extent, tumor localization, later nodal metastasis, and TNM status. Statistical analyses were performed (p < 0.05). Results: A total of 150 patients were identified, 105 receiving unilateral END and 45 bilateral END. The rates of postoperative positive lymph nodes were 21.9% for ipsilateral END and 26.7% for bilateral END (bilateral END: all positive nodes ipsilateral). In all, 14 patients in the ipsilateral group developed nodal metastasis during tumor aftercare (11 patients ipsilateral, 3 patients contralateral neck). In the bilateral group, nodal metastasis was later observed in 4 cases (8.9%; 3 cases ipsilateral, 1 case contralateral neck). Statistical analysis could not detect significant differences between the END procedures. Conclusion: As both procedures lead to similar results in preventing or omitting possible later nodal metastasis, the two methods seem to be valuable alternatives. In conclusion, we recommend bilateral END because of advantages with regard to oncologic safety and esthetic outcome, but the decision for END should always be according to the patient's general health status, comorbidities, and individual tumor risk profile. Highlights: Retrospective comparison of bilateral and unilateral elective neck dissection (END) treatment for early stage unilateral tongue carcinomas (OTSCC). The comparison is focused on the rates of later contra-/ipsilateral nodal metastasis and postoperative positive lymph node rates. Both END procedures show similar results in discovering/neglecting positive lymph nodes or in rates of later nodal metastasis. Bilateral and unilateral END seem therefore to be equal-benefit alternatives for the treatment of early stage OSCC. Bilateral END recommended because of advantages with regard to oncologic safety and esthetic outcome, but decision for END should always be patient-specific.